Understanding Carbon Leakage - Christoph Böhringer; Knut Einar Rosendahl (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
Carbon leakage is a major concern in the design of unilateral climate policies aimed at reducing global emissions in a cost-effective manner. In order to assess the cost-effectiveness of anti-leakage measures, it is crucial to understand the fundamental mechanisms that contribute to leakage. We provide theoretical analysis of the two main channels of leakage: the fossil fuel market channel and the competitiveness channel. We show that the two channels reinforce each other. Furthermore, we find that whereas leakage via the fossil fuel market channel decreases with the fuel supply elasticity and increases with the fuel demand elasticity, the opposite is the case for the competitiveness channel. We show that the effectiveness of output-based allocation and border carbon adjustments to combat carbon leakage increases with the fuel supply elasticity and decreases with the fuel demand elasticity. We supplement the simplified theoretical analysis with numerical simulations using a more complex multi-sector, multi-region computable general equilibrium model of the global economy to quantify the implications of unilateral climate policy designs for the European Union. We find that leakage via the fossil fuel channel dominates leakage via the competitiveness channel unless fuel supply elasticities are quite high and fuel demand elasticities are quite low. Furthermore, we find that the lower the fossil fuel demand elasticity, the greater the gains in cost-effectiveness from implementing anti-leakage measures.
Keywords: D58; F18; H23; Q54; 330; carbon leakage; fossil fuel elasticities; output-based allocation; border carbon adjustments